Anaphore possessive et anaphore associative : le cas des noms collectifs - Mathilde Salles (Discours)
This paper is devoted to some anaphoric operations which are specific to the collection-member relation (e.g., regiment/soldiers, caravan/camels, forest/trees). This relation can be extremely flexible from the anaphoric standpoint, compared to closely related semantic relations such as meronymy (e.g., tree/trunk, car/engine), but can also involve surprising impossibilities. This flexibility and these impossibilities are usually caused, as discussed, by the referential properties of collections (their internal plurality and the homogeneity of their members) and by some semantic properties of the collection-member relation (in particular, the generally non relational nature of the member noun). We study more specifically associative anaphora and possessive anaphora with member nouns. The internal homogeneity of collections explains why associative anaphora is impossible with generic member nouns (relational nouns unlike the others; e.g., member, element): these generic nouns do not allow differentiation while associative anaphora requires differentiation. The generally non relational nature of the member noun explains why possessive anaphora and associative anaphora are not real competitors in other cases. Finally, when all conditions are met for the use of either of the anaphoric processes, we elucidate the consequences of referential choice upon textual coherence relations.